The Impact of Covid-19 on The Effect Multiplier on The Household Consumption Function in Jakarta - Fahrul Riza; Michael Christianto Leonardo (Jambura Equilibrium Journal, 2021)
The purpose of this study is to examine the effect of a decrease in aggregate income, due to activity restrictions during the Covid-19 pandemic, on household consumption expenditure in Jakarta. The research model is based on the Absolute and Permanent income hypothesis, to see the long-term and short-term effects of changes in income on consumption expenditure. The research method is quantitative by using annual data on consumption expenditure and income at current prices for the period 2003 to 2020. The analysis model uses OLS and ECM regression. The results showed that income has a significant effect on the equation of the short-run and long-run consumption function. The short-term income crisis has an impact on the increase in the multiplier coefficient. In the short term there will also be an adjustment in consumption expenditures, according to what is postulated in the permanent income hypothesis. This indicates that in the short term expansionary fiscal policy is effective in increasing aggregate household consumption expenditure. Further research suggests adding the inflation variable as a proxy for economic conditions. Keywords: Absolute Income Hypothesis, Permanent Income Hypothesis, Household Consumption Expenditures, National Income, Multiplier.